2010
DOI: 10.3109/17477160903473739
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between school day sleep duration and body mass index in Norwegian children (aged 10–12)

Abstract: High BMI was associated with short and long self and parent-reported duration of sleep. The percentage of obesity/overweight was higher in the shortest sleep duration group than for intermediate sleep durations. Short sleep duration was significantly associated with obesity but not with overweight. Adjusting for physical maturation and socio-economic status, short sleep duration still showed a significant association with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 37 publications
6
51
3
Order By: Relevance
“…In older children, self-reported sleep duration is probably a more valid measure. A recent study of 10-12-year-old children, however, showed that children's self-reported sleep duration and parents' estimations showed very similar associations with BMI of the child, 5 which indicated a good validity of parents' estimations as compared with self reports. The use of questionnaire data, constructed to study health in general, but not specifically in relation to sleep, limited us to investigate only a selection of factors on the association with sleep duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In older children, self-reported sleep duration is probably a more valid measure. A recent study of 10-12-year-old children, however, showed that children's self-reported sleep duration and parents' estimations showed very similar associations with BMI of the child, 5 which indicated a good validity of parents' estimations as compared with self reports. The use of questionnaire data, constructed to study health in general, but not specifically in relation to sleep, limited us to investigate only a selection of factors on the association with sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…2 Possible explanations for the association between sleep duration and overweight include the role of behavioural and hormonal factors; short sleep leaves more time for eating, particularly snacking or drinking sugared drinks, and causes alterations in appetite-regulating hormones resulting in overeating. 1,2,5 Moreover, sleepiness may result in reduced physical activity and increased sedentary behaviour. 1,2,5 Determinants of short sleep duration have not yet been fully explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, except for a few cross-sectional studies, 13,14 no large prospective studies have examined the relationship between sleep duration and obesity in preschoolaged children, especially the relationship between overlong sleep duration and obesity, which may also be associated with increased risk of obesity. 15 Against these backgrounds, we used the data obtained from the Jiaxing Birth Cohort to explore both the cross-sectional and longitudinal association between sleep duration and overweight/obesity in preschool-aged children. We hypothesized that short sleep duration and overlong sleep duration would both be associated with increased risk of overweight/obesity in preschool-aged children.…”
Section: Significancementioning
confidence: 99%
“…e Includes 58 cross-sectional studies (Al-Hazzaa 2014;Al-Hazzaa et al 2012;Araujo et al 2012;Awad et al 2013;Bawazeer et al 2009;Bel et al 2013;Berentzen et al 2014;Butte et al 2007;Chaput et al 2011Chaput et al , 2014Calamaro et al 2010;Colley et al 2012;Culnan et al 2013;Danielsen et al 2010;de Jong et al 2012;Do et al 2013;Ekstedt et al 2013;Eisenmann et al 2006;Garaulet et al 2011;Guo et al 2012;Gupta et al 2002;Hense et al 2011;Hiscock et al 2011;Hjorth et al 2014aHjorth et al , 2014bHuang et al 2010;Katzmarzyk et al 2015;Knutson 2005;Knutson and Lauderdale 2007;Kong et al 2011;Kuciene and Dulskiene 2014;Lee and Park 2014;Liou et al 2010;Lowry et al 2012;Magee et al 2013a;Martinez-Gomez et al 2011;Meldrum and Restivo 2014;Morley et al 2012;Martinez et al 2014;Ozturk et al 2009;Padez et al 2009;Pallesen et al 2011;Park 2011…”
Section: Harms/injuriesmentioning
confidence: 99%